Поняття та правові засади державної екологічної політики і екологічної безпеки на сучасному етапі розвитку України - Коваленко, І.; Kovalenko, I. (Волин. нац. ун-т. ім. Лесі Українки, 2020)
У статті здійснено спробу дослідити та проаналізувати визначення таких понять як екологічна політика і екологічна безпека, узагальнено основні підходи щодо визначення цих понять. Розглянуті деякі особливості правових засад державної екологічної політики і екологічної безпеки на сучасному етапі розвитку нашої держави. Подолання екологічних загроз та забезпечення екологічної безпеки є складовою державної екологічної політики України. Зроблено висновок, що основна проблема кризової екологічної ситуації полягає в тому, що нормативно-правове закріплення існує, а належного його виконання немає. The article attempts to research and analyze the definition of such concepts as «environmental policy» and «environmental safety» and the principal approaches to the definition of these concepts. The study elucidates some features of the state ecological policy and ecological safety legal regulations at the present stage of our state development. The state policy in the field of environment protection, natural resources utilization, and environmental security is determined as the issue of a top priority for national interests. The author substantiates the need for timely measures, adequate to the nature and the threats rate of environmental security, and proves that they are to be based on the legal principles. Elimination of the environmental threats and providing environmental safety are principal aims of the state environmental policy of Ukraine. The key findings of the study prove that the main problem with the ecological crisis situation in Ukraine is that, despite the fundamental legal framework, the practice lacks its proper implementation.
Ukrainian State Eological Policy and Ecological Safety at the Present Stage of Development: Concepts and Legal Principles
Keywords: державна екологічна політика; правові засади; стратегія; екологічна безпека; навколишнє природне середовище; довкілля; національна безпека; state ecological policy; legal basis; strategy; ecological safety; environment; security